Exploring IoT industry applications limitations of wireless technology on healthcare IoT - Falcone, Francisco (IEEE, 2017)
In this course, we will address the characteristics and limitations imposed by the physical wireless channel, as well as the specifications of communication transceivers employed in order to provide connectivity within m-health/Smart health scenarios. We begin with an initial description of the Physical layer, in terms of understanding coverage/capacity limitations in the use of wireless transceivers. Specific aspects, such as transceiver power and antenna gain will also be highlighted. The second part of the course is devoted to describing the communication systems commonly employed in the provision of wireless connectivity, namely wireless sensor networks, wireless personal area networks, wireless local area networks and mobile communication networks (within the Public Land Mobile Network definition)